(untitled) (Med Phoenix, 2022)
Congenital Pulmonary Airway Malformation (CPAM), previously known as Congenital Cystic Adenomatoid Malformation (CCAM) is a rare dysplastic lesion of the fetal tracheobronchial tree. Here we report a 19 days male child with respiratory distress. Right sided Congenital Pulmonary Airway Malformation Type 1 was diagnosed. Right thoracotomy with upper and middle lobectomy was carried out with successful management of the child.